The Effect of High-Intensity Interval Training on Blood Lactate Levels and Rate of Perceived Exertion in Sedentary Healthy Adults - Nur Ahlina Damayanti; Nury Nusdwinuringtyas; Tresia Fransiska Uliana Tambunan; Aria Kekalih (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2022)
The high-intensity interval training has been seen to be beneficial for various populations. This study aimed to determine the effect of high-intensity interval training (HIIT) on blood lactate levels and rate of perceived exertion (RPE) in sedentary healthy adults. A pre-post study was conducted on adults that were stated healthy and sedentary on physical activity. All participants were given HIIT with a total duration of 20 minutes for 12 sessions using a treadmill. Blood lactate level and RPE was recorded on the 1st and 12th session. A significant decrease in blood lactate level and RPE after giving HIIT was found with a reduction of 1,1 mmol/ L and 2 on the Borg Scale respectively (p<0.0001). Further research is needed using field-based exercise testing to determine exercise prescription and to obtain the benefit of HIIT in populations with cardiovascular risk factors before utilizing it in patients.